2006
DOI: 10.1159/000097672
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial Bicarbonate Transport by Capan-1 Cells: a Model for Human Pancreatic Ductal Secretion

Abstract: Human pancreatic ducts secrete a bicarbonate-rich fluid but our knowledge of the secretory process is based mainly on studies of animal models. Our aim was to determine whether the HCO3- transport mechanisms in a human ductal cell line are similar to those previously identified in guinea-pig pancreatic ducts. Intracellular pH was measured by microfluorometry in Capan-1 cell monolayers grown on permeable filters and loaded with BCECF. Epithelial polarization was assessed by immunolocalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
34
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 40 publications
10
34
0
1
Order By: Relevance
“…In polarised monolayers, ATP and UTP applied luminally stimulated HCO À 3 secretion (measured as decrease in pH i ), while applied basolaterally they inhibited HCO À 3 secretion [104]. This is in agreement with studies on rat and guinea pig pancreatic ducts (see above).…”
Section: Pancreatic Acinisupporting
confidence: 90%
See 2 more Smart Citations
“…In polarised monolayers, ATP and UTP applied luminally stimulated HCO À 3 secretion (measured as decrease in pH i ), while applied basolaterally they inhibited HCO À 3 secretion [104]. This is in agreement with studies on rat and guinea pig pancreatic ducts (see above).…”
Section: Pancreatic Acinisupporting
confidence: 90%
“…This was in fact found in isolated guinea pig pancreatic ducts, where the basolateral application of UTP decreased secretion [103]. A similar effect of UTP on secretory processes was also detected in polarised Capan-1 cells, which are epithelial cells derived from pancreatic adenocarcinoma [104]. RT-PCR analysis of the single rat ducts revealed that they express Ca 2+ -activated K + channels of the intermediate conductance (IK also known as SLO, Maxi K and KCNMA1) and big conductance (BK also known as SK4, KCNN4) [105].…”
Section: Pancreatic Acinisupporting
confidence: 60%
See 1 more Smart Citation
“…As in other epithelia, P2 receptor localisation is difficult to reveal, as the same receptor type can be localised to both luminal and basolateral membranes, though coupled to different ion transporters (Novak 2008(Novak , 2011 (Ishiguro et al 1999, Steward et al 2005, Szücs et al 2006. P2X 7 receptors, most likely luminal, are cation channels but also decrease intracellular pH, possibly reflecting HCO K 3 secretion (Henriksen & Novak 2003).…”
Section: Pancreatic Ductsmentioning
confidence: 99%
“…Secretin action has also been studied in monolayer cultures of canine and bovine pancreatic ducts (26,125) and in Capan-1 cells which are derived from a human tumor but which form a tight monolayer and possess secretin receptors (103,112). Only basic studies have been carried out to date but secretin will increase cAMP and ion transport in these monolayers.…”
Section: In Vitro Studies Of Secretin Action On Pancreatic Ductsmentioning
confidence: 99%